A Causal Model of Social Intelligence of Student-Athlete in Thailand National Sports University Chiang Mai Campus - Chankuna, Dittachai; Sukdee, Thitipong (FOYER: The Journal of Humanities, Social Sciences, and Education, 2024)
The main objective of this research is to analyze a causal model of social intelligence. A sample of 232 people was selected using a multi-stage sampling method. The sample was drawn from student-athletes at the Thailand National Sports University, Chiang Mai campus. Research instruments were five questionnaires with rating-scales, which developed based on previous research. Confirmatory factor analysis and structural equation modeling were employed to work out the causal model. The results showed that the sample's average social intelligence scores across all aspects were at the highest level. Fifteen variables in the hypothesis model were extracted into five factors with a comparative fit index (CFI at 0.972) in an appropriate manner. The causal model of social intelligence comprised a Model of adaptation, Family relations, University environment, Emotional quotient, and social intelligence. University environment was the most influential. The value of this research lies in the discovery of a causal model of social intelligence. Administrators at educational institutions could consider implementing support policies for student-athletes aimed at developing social intelligence by managing the institutional environment.